Peningkatan Sikap Moderat Remaja Melalui IPNU-IPPNU di Desa Bekiring - Hanafia, Maskur; Susanto, Hanafi Hadi (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Along with the emergence of complaints and problems faced by the NU Branch Management and the community in Bekiring Village, Pulung regarding increasing and strengthening the moderate attitude of youth who are not facilitated. From this, a solution emerged so that teenagers could be facilitated by how the moderate attitude of teenagers increased and became stronger, namely by forming an organized organization under the auspices of the Nahdlatul 'Ulama which is commonly called the Nahdlatul 'Ulama Student Association (IPNU) and the Nahdlatul 'Ulama Female Student Association (IPPNU). This program was assisted and accompanied by participants in the Community Service Lecture (KPM) group 3 of INSURI Ponorogo. This organization can become a bridge to improve and strengthen the moderate attitude of youth in Bekiring Village, which is the hope of the NU Branch Management and the local community. The methodology used in this program is through the coaching and actualization stages. Coaching is carried out by providing insight and understanding of organization, national insight and moderate attitudes among Jam'iyyah Nahdlatul 'Ulama. The results of increasing the moderate attitude of teenagers in this program can be seen from how the process is carried out during the coaching period and providing insight about moderation. And it can be concluded that the provision of guidance and insight into moderate attitudes can increase the moderate attitude of youth through the IPNU-IPPNU forum in Bekiring Village.